PENGARUH INTENSITAS MODAL DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK PERUSAHAAN PENGHASIL BAHAN BAKU SUB SEKTOR PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BEI 2017-2019 - Sabatini Simbolon; Lorina Siregar Sudjiman (Jurnal Ekonomis, 2021)
This study aims to see how capital intensity, how leverage, how tax aggressiveness, and how capital intensity and leverage on tax aggressiveness. This research was conducted at companies producing raw materials for coal mining sub-sector which were listed on the Indonesia Stock Exchange (IDX) in 2017-2019 and using a purposive sampling sample of 20 companies for 3 years of research, the number of sampling was 60 observation data. The population in this study is the annual financial statements of all mining sub-sector producing companies listed on the Indonesia Stock Exchange (BEI) 2017-2019. The analytical methods used in managing statistical data analysis are normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, t test and f test. Based on the simultaneous test results, capital intensity and leverage have a significant effect on tax avoidance in Coal Mining Sub-Sector Raw Material companies listed on the Indonesia Stock Exchange in 2017-2019.